A linear-to-circular polarization converter based on I-shaped circular frequency selective surfaces - 吴家梁 林宝勤 达新宇 吴凯 (Chinese physics B, 2017)
In this paper, a linear-to-circular polarization converter using a three-layer frequency selective surface based on Ishaped circular structure resonant is presented and investigated. Numerical simulations exhibit that when the normal ypolarized waves impinge on this device propagating towards ＋z direction, the two orthogonal components of the transmitted waves have a 90° phase difference as well as the nearly equal amplitudes at the resonant frequency of 7.04 GHz, which means that the left-hand circular polarization is realized in transmission. For validating the proposed design, a prototype which consists of 25 × 25 elements has been designed, manufactured and measured. The measured results are in good agreement with the simulated ones, showing that the polarization conversion transmission is over-3 dB in the frequency range of 5.22–8.08 GHz and the axial ratio is below 3 dB from 5.86 GHz to 7.34 GHz.